A bibliometric analysis of a decade’s research on metabolic dysfunction-associated steatotic liver disease in the Arab world - Waleed Alhazzani; Shadan AlMuhaidib; Haifa F. Alotaibi; Waleed S. Alomaim; Rawan Alqahtani; Faisal M. Sanai; Faisal Abaalkhail; Saleh A. Alqahtani (The Saudi Journal of Gastroenterology)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) presents a significant global health challenge, with the Arab region exhibiting a markedly higher prevalence. We aim to evaluate MASLD research output, collaboration patterns, and funding impact in the Arab region over the last decade. Methods: We conducted a bibliometric analysis of MASLD research in 22 Arab countries (2014–2023) using Clarivate Analytics’ InCites. Data on MASLD prevalence were extracted from the Global Burden of Disease, while population and economic data from the World Bank. We assessed MASLD-related publications, prevalence, collaboration patterns, and citation and funding impact. Results: Between 2014 and 2023, Arab countries contributed 844 publications (3.3% of global MASLD research). We identified positive correlations between MASLD-related publications and gross domestic product (GDP) (rs = 0.825, P < 0.001), age-standardized prevalence (rs = 0.627, P = 0.002), and population size (rs = 0.509, P = 0.016). International collaborations accounted for 48.7% of these publications, with a citation impact of 15.7 compared to the global average of 23.7. Arab-funded MASLD-related publications constituted 19.4% of MASLD publications in the Arab world versus 42.3% globally funded. Citation impacts were similar between Arab-funded (30.6) and globally funded publications (30.3). Of the top 10 countries globally with the highest GDP, 47.8% of the MASLD publications received funding, yielding a citation impact of 33.5. Conclusion: Despite the high MASLD prevalence, Arab countries exhibit lower research output, impact, and funding compared to global levels. Increased regional collaboration and investment in MASLD research are critical to addressing this disparity.